2004
DOI: 10.1038/sj.ejcn.1601934
|View full text |Cite
|
Sign up to set email alerts
|

Effects of trans- and n-3 unsaturated fatty acids on cardiovascular risk markers in healthy males. An 8 weeks dietary intervention study

Abstract: Background: Studies of long-term intake of industrially produced trans fatty acids (TFA) and n-3 polyunsaturated fatty acids (PUFA) suggest opposite effects on cardiovascular disease risk. Common mechanisms of action are probable. Objective: To examine the effects on cardiovascular risk markers of dietary enrichment with TFA or n-3 PUFA. Design: Randomized, double-blind, parallel intervention trial. Setting: Department of Human Nutrition, The Royal Veterinary and Agricultural University. Subjects: In all, 87 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
3
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(70 citation statements)
references
References 33 publications
0
65
3
2
Order By: Relevance
“…A positive association between n-3 PUFAs and HRV has been observed in patients with type 1 diabetes mellitus (DM) (7), in those with coronary heart disease (8,9) as well as in healthy subjects (10)(11)(12)(13). In contrast, no changes in HRV parameters were observed in some studies conducted among healthy subjects (14)(15)(16) and haemodialysis patients (17). Regarding HR, a beneficial impact of n-3 PUFAs has been observed among coronary artery disease patients (18) and among healthy subjects (3,19,20).…”
Section: Introductionmentioning
confidence: 82%
“…A positive association between n-3 PUFAs and HRV has been observed in patients with type 1 diabetes mellitus (DM) (7), in those with coronary heart disease (8,9) as well as in healthy subjects (10)(11)(12)(13). In contrast, no changes in HRV parameters were observed in some studies conducted among healthy subjects (14)(15)(16) and haemodialysis patients (17). Regarding HR, a beneficial impact of n-3 PUFAs has been observed among coronary artery disease patients (18) and among healthy subjects (3,19,20).…”
Section: Introductionmentioning
confidence: 82%
“…18) Previous studies have examined the influence of n-3 PUFAs on autonomic activity analyzed by the power spectral and time-domain methods. [19][20][21][22][23] Some studies showed a positive association between n-3 PUFAs and HRV in patients with ischemic heart disease 19) and, in those with dilated cardiomyopathy 20) as well as in healthy subjects. 21) In contrast, no changes in HRV parameters were observed in some studies conducted among healthy subjects and haemodialysis patients.…”
Section: )mentioning
confidence: 99%
“…Trans FA are of exogenous origin. Their atherogenic effect 44 is assumed to be greater than that of SFA. Also, trans MFA are twice as active in raising LDL-cholesterol and decreasing HDL-cholesterol than SFA.…”
Section: Monounsaturated Fatty Acids In Trans Configurationmentioning
confidence: 99%